Nilai Kearifan Lokal dalam Naskah Panji Salatin (Refleksi Filologis Manuskrip Kesultanan Kutai Kartanegara) - Iskandar Iskandar; Materan Materan (FENOMENA, 2021)
The Panji Salatin manuscript is one of the most important cultural heritages in the history of the Kutai Kartanegara sultanate. The manuscript, which was born during the reign of Prince Aji Sinum Panji Mendapa (1635-1650), contains the sultanate laws and became the most decisive beginning in the administration of the next government system. This study aims to describe and explain the value of local wisdom contained in the Panji Salatin manuscript. This research is based on philological reflection with a phenomenological, historical approach to interpreting the text. The source of the data used is a copy of the Manuscript Law on the Banner of Salatin, which is stored in the Mulawarman Tenggarong Museum, Kutai Kartanegara. The results of the analysis of the text units contained in the Panji Salatin manuscript show that: 1). religion and culture become sources of norms and ethics that coexist (syariat menaiki-adat menuruni), then the style of religion becomes open to culture 2). The king/Sultan must be a symbol of protection for the people, and the people must be loyal to the king/Sultan, then the rule of â€œpeopleâ€™s religion is the kingâ€™s religionâ€ 3). The king/sultan and his subordinates are both subject to a system of deliberation and consensus with the ulama. All have equal standing before the law. This principle of unity and togetherness contains a very strong relationship with traditional cultural ceremonies, namely â€œerauâ€ as a party, not only for the people but even as a symbol of justification for the power of the sultan/king.